Exploring the Role of Functions of Attitude toward Perceived Cultural Distance in Intercultural Service Encounters (ICSE) - Daneshfar, Zahra; Sharma, Piyush; Kingshott, Russel (2020)
As immigration and international tourism is increasing exponentially, it is important to study factors affecting intercultural service encounters (ICSE). This research extends ICSE framework by developing a conceptual model using the functional theory of attitude and service-dominant logic. We propose functions serve by attitude toward perceived cultural distance (i.e. value-expressive, social-adjustive, ego-defensive, knowledge, and utilitarian) affects interaction comfort and inter-role congruence. We also raise argument about predictors of one’s willingness to co-create in ICSE as well as the role of intercultural competence. Findings from a qualitative study support the proposed linkages. These findings help managers understand how customers’ and employees’ attitudes in ICSE is shaped and how they can manage it in order to improve the service outcomes.